Elevated serum ferritin level associated with hepatic steatosis and fibrosis in hepatitis C virus–infected patients. Issue 2 (February 2019) - Batsaikhan, Batbold; Gantumur, Gantsetseg; Huang, Ching-I; Yeh, Ming-Lun; Huang, Chung-Feng; Lin, Zu-Yau; Chen, Shinn-Cherng; Huang, Jee-Fu; Yu, Ming-Lung; Chuang, Wan-Long; Lee, Jin-Ching; Dai, Chia-Yen
Abstract : Background: Serum ferritin is an indicator of iron accumulation in a human body, and it is frequently elevated in patients with systemic inflammatory state in chronic hepatitis C (CHC). Iron accumulation is associated with hepatic fibrosis, steatosis, and unfavorable outcome in CHC patients. We studied the status of elevated serum ferritin level and its association with the liver fibrosis or steatosis in Taiwanese CHC patients. Methods: Seven hundred and thirty-eight Taiwanese CHC patients were consecutively included in this study. Laboratory analysis, four indexes of fibrosis (FIB4), histological assessment of fibrosis, and steatosis were assessed by appropriate elevation of serum ferritin level. Results: Three hundred and one patients (40.8%) had elevated serum ferritin level (sex-specific threshold >1.5 × upper limit of normal). Serum iron level (odds ratio [OR], 1.02; 95% CI, 1.01%-1.03%, p < 0.001), female gender (OR, 1.49; 95% CI, 1.07%-2.08%, p = 0.018), serum gamma-glutamyl transferase level (OR, 1.007; 95% CI, 1.003%-1.01%, p < 0.001), steatosis grade (OR, 1.56; 95% CI, 1.13%-2.16%, p = 0.006), and FIB4 ≥3.25 (OR, 1.63; 95% CI, 1.18%-2.27%, p = 0.003) indexes were associated with high serum ferritin level by multivariate logistic regression analysis. Patients with steatosis (>5%) were associated with older age (OR, 1.01; 95% CI, 1.00%-1.03%, p = 0.015), body mass index (OR, 1.10; 95% CI, 1.05%-1.15%, p < 0.001), and elevated serum ferritin level (OR, 1.001; 95% CI, 1.00%-1.001%, p = 0.024) by multivariate logistic regression analysis. Serum ferritin level also associated with high FIB4 (≥3.25) (OR, 1.001; 95% CI, 1.001%-1.002%, p = 0.010) when multivariate model adjusted together with advanced liver fibrosis by biopsy. Conclusion: Elevated serum ferritin level was noted in 40.8% of Taiwanese CHC patients, and the serum ferritin level was associated with liver steatosis and high FIB4.